Precambrian Nomenclature in Kansas - Sawin, Robert S.; Franseen, Evan K.; Ludvigson, Greg A.; Watney, W. Lynn; West, Ronald R. (Current Research in Earth Sciences, 2013)
The informal stratigraphic term "Precambrian" is replaced by formal nomenclature–Proterozoic and Archean Eonothems/Eons–and the informal term Hadean. The Phanerozoic Eonothem/Eon, representing all rocks younger than the Proterozoic, is added. The Proterozoic is further divided into Paleoproterozoic, Mesoproterozoic, and Neoproterozoic Erathems/Eras. The name Rice Formation (Scott, 1966) is abandoned, and the use of the informal term "Rice unit" is recommended. The proposed name Rice Series (Berendsen, 1994) is not accepted. These changes are adopted by the Kansas Geological Survey (KGS) and the stratigraphic nomenclature of Zeller (1968) has been revised accordingly.